Penguasaan Hak Atas Tanah Berdasarkan Perjanjian Nominee dalam Investasi Asing di Indonesia - Gilbert Parulian Naibaho; Ni Luh Made Mahendrawati; I Wayan Rideng (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the legal provisions on land rights for foreign nationals in the Indonesian land law system and to examine the validity and legal consequences of nominee agreements in the control of land rights by foreign investors. The background of this study is based on the practice of using nominee agreements (borrowing names) by foreign nationals to control land in Indonesia, which legally contradicts the provisions of the Basic Agrarian Law (UUPA) which prohibits ownership of land rights by foreign parties. This study uses a normative legal research method with a legislative approach and a conceptual approach. The legal sources used include primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study indicate that the regulation of land rights for foreign nationals in the Indonesian legal system is limited to use rights, lease rights, or through certain legal entities such as Foreign Investment Limited Liability Companies (PT PMA). Meanwhile, the practice of nominee agreements is a form of legal smuggling that contradicts the basic principles of national agrarian law, so that the agreement can be declared null and void. In addition, this practice creates legal uncertainty and has the potential to harm the state and society because it obscures the status of land ownership. In conclusion, firm law enforcement and regulatory harmonization between agrarian and investment law are needed to ensure legal certainty and safeguard state sovereignty over land, without hindering foreign investment in Indonesia.